2008
DOI: 10.1016/j.cell.2008.06.048
|View full text |Cite
|
Sign up to set email alerts
|

UBXD7 Binds Multiple Ubiquitin Ligases and Implicates p97 in HIF1α Turnover

Abstract: p97 is an ATP-dependent chaperone that plays an important role in endoplasmic reticulum-associated degradation but whose connections to turnover of soluble proteins remain sparse. Binding of p97 to substrates is mediated by cofactors that contain ubiquitin-binding domains. We employed "network proteomics" to show that p97 assembles with all of the 13 mammalian UBX-domain proteins. The UBX proteins that bind ubiquitin conjugates also interact with dozens of E3 ubiquitin ligases, only one of which had been previ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
380
2
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 289 publications
(409 citation statements)
references
References 63 publications
26
380
2
1
Order By: Relevance
“…Indeed, it was shown that immunoprecipitates of the UBA-UBX proteins FAF1, UBXD7, UBXD8 and SAKS1 contained not only p97, but also UFD1-NPL4 [49], an observation that is consistent with the existence of higher-order p97-cofactor complexes. A similar observation was made in yeast where the UBA-UBX protein Ubx2 was found to exist in a Cdc48 Ufd1-Npl4-Ubx2 complex [108].…”
Section: Higher Order Assembliessupporting
confidence: 58%
See 2 more Smart Citations
“…Indeed, it was shown that immunoprecipitates of the UBA-UBX proteins FAF1, UBXD7, UBXD8 and SAKS1 contained not only p97, but also UFD1-NPL4 [49], an observation that is consistent with the existence of higher-order p97-cofactor complexes. A similar observation was made in yeast where the UBA-UBX protein Ubx2 was found to exist in a Cdc48 Ufd1-Npl4-Ubx2 complex [108].…”
Section: Higher Order Assembliessupporting
confidence: 58%
“…These UBA-UBX proteins serve as prototypical substrate-recruiting cofactors or substrate ''adaptors" of p97. So far, 13 UBX domain-containing proteins have been identified in mammals, all of which, with the exception of UBXD1 (see below), have been demonstrated to bind to p97 [46,47,49]. In addition, the related UBXL domain has been identified in a few p97 cofactors including the NPL4 subunit of the heterodimeric UFD1-NPL4 cofactor [50] and the two DUBs OTU1/YOD1 [51] and VCIP135 [52].…”
Section: Ubx and Ubxl Domainsmentioning
confidence: 99%
See 1 more Smart Citation
“…The phenotypes observed after co-depletion of Ube2S and UbcH10 are reminiscent of the strong mitotic delay caused by injection of a K11-deficient ubiquitin mutant into Xenopus embryos (11). A proteomic analysis revealed that p97/CDC48, whose depletion causes mitotic arrest in HeLa cells (39), efficiently binds K11-linked ubiquitin chains (40). K11-linked ubiquitin chains also accumulate in diseases with impaired proteasome activity, such as Huntington's or Alzheimer's (41), and they are abundant in normally dividing cells (12).…”
Section: Discussionmentioning
confidence: 99%
“…In recent studies, the ATPase p97/VCP of the AAA (ATPases associated with diverse cellular activities) family has been implicated in the proteasomal degradation of certain cytosolic substrates (9)(10)(11)(12)(13). VCP is capable of dissociating proteins from large cellular structures such as the endoplasmic reticulum (14), the mitotic spindle (12), the nuclear envelope (15), and chromatin (16).…”
Section: Intracellular Immunity | Cdc48mentioning
confidence: 99%